(untitled) (Global Journal of Science Frontier Research, 2016)
Three sedges of Cyperus (C. malaccensis, C. compressus and C. iria) are used for making mats by the forest fringe people of Sunderban mangrove swamp and sale in local markets. The focus of the work is to calculate species wise net economic contribution of these sedges. Fifteen families from each four villages of two islands have been selected for qualitative and quantitative assessment of these resource use pattern through participatory observation and questionnaire method. The annual production, economic valuation of individual species were assessed through quadrat sampling (272 habitat patch) and market survey with cost benefit analysis respectively. Economic contribution of the sedges to the local people in terms of annual income is highest in case of C. malaccensis (6.638%) followed by C. compressus (1.599%) and C. iria (0.690%). The production of the three species is 5-8 times higher than paddy, thus have potentiality as alternative livelihood options.